Interface effects in the phase determination of Hf0.5Zr0.5O2 epitaxial thin films - Jesse Schimpf; Wang Zhang; Mahir Manna; Sandhya Susarla; Xue-Zeng Lu; James M. Rondinelli; Lane W. Martin (APL Materials)
HfO2-based ferroelectrics show tremendous potential for applications in computing technologies, but questions remain as to what dictates the stabilization of the desired phase. Here, it is demonstrated that the substrate the film is grown on is more influential than factors such as thickness, defect content, and strain. The presence of different possible polymorphs of Hf0.5Zr0.5O2 are observed to vary widely for different substrate materials—with La0.67Sr0.33MnO3, (LaAlO3)0.3(Sr2AlTaO6)0.7, and Al2O3 being (more) optimal for stabilizing the ferroelectric-orthorhombic phase. This substrate effect is found to be more influential than any changes observed from varying the film thickness (7.5–60 nm), deposition environment (oxygen vs argon), and annealing temperature (400–600 °C) in vacuum (10−5 Torr). X-ray diffraction and scanning transmission electron microscopy verify the phases present, and capacitor-based studies reveal ferroelectric behavior (or lack thereof) consistent with the phases observed. First-principles calculations suggest that forming oxygen vacancies in Hf0.5Zr0.5O2 lowers its work function, driving electrons away and helping to stabilize the ferroelectric phase. Substrates with a high work function (e.g., La0.67Sr0.33MnO3) facilitate this electron transfer but must also have sufficient ion conductivity to support oxygen-vacancy formation in Hf0.5Zr0.5O2. Together, these observations help clarify key factors essential to the stabilization of HfO2-based ferroelectrics.